El hombre que se convirtio en toro y otras historias de la Inquisicion - Cortes Hernandez, Santiago; Clement, Edgar (Mexico, D. F. : Castillo, 2006)
Stories from the history of the Inquisition in New Spain.
Keywords: Inquisition -- New Spain -- Juvenile literature; Inquisition -- Mexico -- San Juan del Rio (Queretaro) -- Juvenile literature; Inquisicion -- Nueva Espana -- Literatura juvenil; Inquisicion -- Mexico -- San Juan del Rio (Queretaro) -- Literatura juvenil; New Spain -- History -- Juvenile literature; Nueva Espana -- Historia -- Literatura juvenil